2004
DOI: 10.1309/b8tc-0lbv-h8xy-5mfv
|View full text |Cite
|
Sign up to set email alerts
|

Immunostaining for Human Herpesvirus 8 Latent Nuclear Antigen-1 Helps Distinguish Kaposi Sarcoma From Its Mimickers

Abstract: We assessed the usefulness of a mouse monoclonal antibody (13B10) against human herpesvirus 8 (HHV-8) latent nuclear antigen-1 (LNA-1) in diagnosis of Kaposi sarcoma (KS) and for distinguishing it from various mimickers by studying 50 cases of KS and 53 mimickers (angiosarcoma, 15; kaposiform hemangioendothelioma, 6; spindle cell hemangioma, 3; reactive angioendotheliomatosis, 3; bacillary angiomatosis, 4; acroangiomatous dematitis, 2; microvenular hemangioma, 2; hobnail hemangioma, 2; pyogenic granuloma, 5; d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 23 publications
1
47
1
3
Order By: Relevance
“…In certain areas of our country classical-type KS is a commonly encountered cutaneous vascular neoplasm. Thus, knowledge of the histological subtypes and a search for the presence of the virus HHV-8 in cases suspected for KS are important for differential diagnosis [911]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In certain areas of our country classical-type KS is a commonly encountered cutaneous vascular neoplasm. Thus, knowledge of the histological subtypes and a search for the presence of the virus HHV-8 in cases suspected for KS are important for differential diagnosis [911]. …”
Section: Discussionmentioning
confidence: 99%
“…In KS spindle cells and neoplastic vascular structures react positively with endothelial markers (e.g., CD31, CD34, and D2-40) [1]. The most important point in the diagnosis of KS is to show HHV-8 immunopositivity supporting histological findings in the neoplastic component [911]. …”
Section: Introductionmentioning
confidence: 99%
“…LANA-1 protein may cause dysfunction of cell cycle regulatory checkpoints by degrading p53 and inactivating pRb 37. It has been previously shown that positive immunostaining for HHV8 LANA-1 exhibits high sensitivity and specificity, and it is a reliable and cost-effective method for the diagnosis of KS and is also useful for distinguishing it from the mimickers 21,25,29…”
Section: Biomarkers Used In Hiv-ks Diagnosis/prognosismentioning
confidence: 99%
“…19 Currently our laboratory performs oestrogen, progesterone and HER2 staining for breast cancer treatment following guidelines, 20,21 differentiation of lymphomas using a basic panel of antibodies, 22,23 research-based diagnostics for Kaposi’s sarcoma (KS) using latency-associated nuclear antigen (LANA-1) and Wilm’s tumour. This work helps to facilitate treatment of patients, avoid treatment of clinically ambiguous presentations of disease as cancer 24 and more efficiently utilise limited treatment resources.…”
Section: Discussionmentioning
confidence: 99%